A cost-effective solution to power the gate drivers of multilevel inverters using the bootstrap power supply technique - Klumpner, Christian; Shattock, Nicholas (2009)
Multilevel inverters are traditionally seen as a step forward in DC/AC conversion, providing more output voltage levels, better quality of the generated waveform and lower switching losses than the two-level and can process higher voltages with a given forced commutated switch technology. There are also drawbacks associated with this technology: more switching devices and associated gate driver circuitry, more complex modulation and control of the DC-link capacitor voltage sharing etc, which as of now limit its application to the high voltage/power range. This paper proposes a cost-effective solution to implement the power supply needed for powering the gate drivers based on the bootstrap supply technology, which will not need isolated DC/DC supplies for each gate driver, reducing the overall cost of a multilevel assembly and making it more appealing for lower power applications.